Electronic structures and physical properties of double perovskite A2CoNbO6 (A = Sr, Ba) crystals. (30th December 2019) - He, Dafang; Du, Xue; Mei, Huayue; Zhong, Yuhan; Cheng, Nanpu
Abstract: The crystal structures, mechanical properties, lattice dynamics, electronic structures and optical properties of Sr2 CoNbO6 and Ba2 CoNbO6 have been studied by the first principles of density functional theory. The theoretically obtained crystal parameters of Sr2 CoNbO6 and Ba2 CoNbO6 are consistent with their experimental ones. Both Sr2 CoNbO6 and Ba2 CoNbO6 belong to the space group at the low-temperature limit and have very weak elastic anisotropy. The former is slightly brittle while the latter is more brittle. Their electronic structures are similar to each other, and Co-3 d and O-2 p   orbitals constitute the top valence bands while Co-3 d orbitals form the bottom conduction bands. Sr2 CoNbO6 and Ba2 CoNbO6 are indirect band gap semiconductors, and their band gaps are respectively 2.916 and 3.050 eV. The close band gaps are mainly dominated by the similar octahedrons in their crystal structures. The electron transitions from O-2 p   orbitals in the valence bands to Co-3 d orbitals in the conduction bands play important roles in the optical properties of Sr2 CoNbO6 and Ba2 CoNbO6 . Due to the same point group, Sr2 CoNbO6 and Ba2 CoNbO6 have the same five active lattice vibration modes of, , , and and one static lattice vibration mode of, and the typical displacement patterns are also analyzed in detail.